Impacts of Gender Based Violence on Women’s Overall Psychological, Social and Economic Wellbeing. A Case Study in Ijumo Sub-County, Mitooma District - Gina Ashaba (Uganda Christian University, 2024)
This research report was conducted to investigate the impacts of gender-based violence on women’s overall psychological, social and economic wellbeing in Mitooma District, specifically focusing on Ijumo sub-county. The study was guided by three objectives; to examine the current forms of gender-based violence in Ijumo sub-county Mitooma district, to examine the mechanisms of local government authorities in resolving GBV on women in Ijumo sub-county Mitooma District and to identify the measures taken to reduce gender-based violence in Ijumo sub-county Mitooma District. The researcher utilized a sample of 56 respondents and employed a mixed method approach to gather data. The findings revealed that most respondents of 60% agreed that they had experienced forms of gender-based violence in their lifetime. Then 7.1% of the respondents identified alcohol/ drug abuse as a common trigger for gender-based violence in their community, 60.7% identified economic stress, 10.7% identified cultural practices and 7.1% identified triggers for gender-based violence. A significant percentage of the respondents 64.3% believe that GBV is a serious issue in the community, but however, a reasonable percentage 35.7% didn’t believe implying that GBV to a small extent is a serious issue in the community. The study highlights the need for the government to strengthen policies addressing gender-based violence and for local leaders and citizens to collaborate closely to provide effective support to the victims. Community and local leaders should also educate and create awareness about the impacts of gender-based violence on women psychological, social and economic wellbeing.
Undergraduate dissertation